Coğrafya öğrenmek niçin önemlidir? Lise öğrencilerinin algıları - KOCALAR, ALİ OSMAN (My University, 2014)
Bu araştırma, lise öğrencilerinin coğrafya öğrenmenin önemine ilişkin görüşlerini belirlemek amacıyla yapılmıştır. Araştırmaya 2013-2014 öğretim yılı ikinci döneminde İstanbul’daki bir Fen Lisesi, bir Sosyal Bilimler Lisesi ve bir Anadolu Lisesinde öğrenim gören 139 öğrenci katılmıştır. Araştırmada nitel fenomenolojik araştırma deseni kullanılmıştır. Katılımcıların coğrafya öğrenmenin önemine ilişkin görüşlerini belirlemek için yarı yapılandırılmış görüşme formu kullanılmıştır. Elde edilen veriler içerik analizi yoluyla değerlendirilmiştir. Araştırma sonucunda, coğrafya öğrenmenin önemine yönelik farklı kategoriler oluşturulmuştur.

This study was carried out to indicate high school students’ perception on importance of learning geography. Qualitative phenomenological method of study was used to understand the students’ perception. Semi-structured interviews were used to report the perception of participants about the importance of learning geography. Interviews were conducted with 139 high school students at one science high school, one social sciences high school and one Anatolian high school in İstanbul in 2013-2014 academic year second semester. At the assessment phase, a content analysis was implemented. To analyze the data, students’definitions were categorized and the frequency of each category were determined.
Keywords: Lise; coğrafya öğrenimi; coğrafya öğrenmenin önemi; nitel araştırma; öğrenci algısı; High school; geography; importance of learning geography; qualitative research; student perception